2022
DOI: 10.1073/pnas.2116818119
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection induces higher trust in strangers

Abstract: How does the COVID-19 pandemic affect interpersonal trust? Most evidence shows that natural disasters reinforce trust and cooperation, but the COVID-19 virus differs from other calamities, since it spreads through contact with people, potentially increasing suspicion and distrust, as, according to contemporaneous writers’ accounts, seems to have been the case with the Black Death, the London plague, and the Spanish influenza. We investigate the link between interpersonal trust and individuals exposed to COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…The outcomes for the effect of pandemic on trust show mixed results. Most studies report that direct or indirect exposure to the Covid-19 has no effect on the general or interpersonal trust (Brück et al, 2020;Bellani et al, 2022;Bogliacino et al, 2021) while other report it either increased (Gambetta & Morisi 2022) or decreased (Daniele et al, 2020) trust. A second set of studies compare trust measured pre-and after the start of pandemic and most of them report no change (Heap et al, 2021;Lohmann et al, 2023;Umer, 2023), while some report decreased (Li et al, 2020) or increased trust (Esaiasson et al, 2021;Sibley et al, 2020).…”
Section: Trustmentioning
confidence: 99%
“…The outcomes for the effect of pandemic on trust show mixed results. Most studies report that direct or indirect exposure to the Covid-19 has no effect on the general or interpersonal trust (Brück et al, 2020;Bellani et al, 2022;Bogliacino et al, 2021) while other report it either increased (Gambetta & Morisi 2022) or decreased (Daniele et al, 2020) trust. A second set of studies compare trust measured pre-and after the start of pandemic and most of them report no change (Heap et al, 2021;Lohmann et al, 2023;Umer, 2023), while some report decreased (Li et al, 2020) or increased trust (Esaiasson et al, 2021;Sibley et al, 2020).…”
Section: Trustmentioning
confidence: 99%
“…A study conducted in Norway found no overall increase in generalized trust in the early phase of the pandemic, which was, however, higher for individuals who had a direct experience with the disease compared to those who perceived themselves as at risk or were worried about the pandemic [27]. Research [28] found a generalized increase in interpersonal trust during the COVID-19 pandemic compared to the pre-pandemic level among the Italian population and increased levels of trust in strangers among people who caught COVID-19. Different results for social and political trust emerged in China, where greater exposure to COVID-19 risks significantly decreased general and political trust among the adult population [29].…”
Section: Social and General Trust During The Outbreak Of Covid-19mentioning
confidence: 99%
“…These acts come at a cost to the individual (e.g., social isolation), but are beneficial to the group as a whole (e.g., safeguarding vulnerable groups; i.e., a societal conundrum) [18]. A recent study revealed that educating individuals about the dangers the pandemic poses to their health significantly increased their trust in strangers [19].…”
Section: Public Trust and Perceived Societal Fairnessmentioning
confidence: 99%
“…In the present study, several indices of public trust relevant to the COVID-19 pandemic were included: trust in local government officials, doctors, and strangers [12,18,19]. Local government officials and doctors are cooperating to initiate response and communicate the corresponding reasons to the public [12].…”
Section: Public Trust and Perceived Societal Fairnessmentioning
confidence: 99%
See 1 more Smart Citation